Anti-Inflammatory and Pro-Resolving Effects of N-3 PUFA in Cancers: Structures and Mechanisms - Wang, Qi; Hu, Minghua; Xu, Huibi; Yang, Xiangliang (Current Topics in Medicinal Chemistry, 2016)
As an important hallmark in cancer progress, inflammation attracts more and more interests in recent years. Lots of evidences support the positive effect of n-3 PUFA in inflammation-associated diseases, the supplement of these fatty acids is thought to be promising in the prevention and treatment of cancers. In this review, we summarize some current knowledge of the mechanisms by which n-3 PUFA are thought to attenuate cancer associated inflammation, and we also introduce the current situation of n-3 PUFA in clinic.
Keywords: Specialized pro-resolving mediators